Faktor Faktor yang Berhubungan dengan Perilaku Merokok pada Remaja di SMKN 1 Ulu Moroo Kabupaten Nias Barat - Gulo, Maria Dilia; Widani, Ni Luh (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2025)
Cigarettes contain harmful substances such as nicotine, tar and carbon monoxide which are harmful to the body which can cause cancer, chronic obstructive pulmonary disease, coronary heart disease, tuberculosis, stroke, the younger the age of smoking the more at risk of affecting health. The purpose of the study was to determine the factors associated with smoking behaviour in adolescents at SMK UMO. Quantitative research method, descriptive correlation. Sampling with total sampling, as many as 100 students. Data collection in May 2024, using a questionnaire that has been tested for validity and reliability. The results of univariate analysis showed that the majority of respondents had sufficient knowledge 54.0%, positive attitude category 62.0%, influenced by peers 62.0%, influenced by family 66.0%, and influenced by advertising 57.0%. The results of bivariate analysis of kendall's Tahu B obtained there is a significant relationship between influenced peers with smoking behaviour with a p-value of 0.002 (p <0.05). There is no significant relationship between attitude p-value 0.205, family influence p-value 0.150, advertising influence p-value 0.228, knowledge p-value 0.893; (p>0.05), Conclusion, there is a relationship between peer influence and adolescent smoking behaviour at SMK UMO. Recommendation : To the school can make preventive efforts by providing education to students about the dangers of smoking, and adolescents are expected to have a strong commitment not to smoke and avoid promiscuity from the surrounding environment. Keywords: smoking behaviour, adolescents